A practical laboratory method to determine ceftazidime-avibactam-aztreonam synergy in patients with New Delhi metallo-beta-lactamase (NDM)–producing Enterobacterales infection. (June 2022) - Rawson, Timothy Miles; Brzeska-Trafny, Ilona; Maxfield, Rosemary; Almeida, Manfred; Gilchrist, Mark; Gonzalo, Ximena; Moore, Luke SP; Donaldson, Hugo; Davies, Frances
Highlights: We evaluated a practical laboratory method of testing for clinically significant synergy between combination antimicrobial therapy with ceftazidime/avibactam plus aztreonam (CAZ/AVI+ATM) in New Delhi metallo-beta-lactamase (NDM)–producing Enterobacterales using an Etest/disc method. Using the broth dilution method, 33 of 43 isolates (77%) were ATM resistant (median [range] minimum inhibitory concentration [MIC] = 56 [16–512] mg/L). The addition of CAZ/AVI restored the ATM breakpoint (MIC < 4 mg/L) in 29 of 33 resistant isolates (89%) using broth dilution. The Etest/disc method correlated with findings from broth dilution in 35 of 43 cases (81%). Etest/disc sensitivity was 77% and specificity was 85%. Positive predictive value was 92% and negative predictive value was 61%. ABSTRACT: Objectives: In response to infection with New Delhi metallo-beta-lactamase (NDM)–producing Enterobacterales, combination antimicrobial therapy with ceftazidime/avibactam (CAZ/AVI) plus aztreonam (ATM) has been explored. This study evaluated a practical laboratory method of testing for clinically significant synergy between CAZ/AVI+ATM in NDM-producing Enterobacterales. Methods: Minimum inhibitory concentrations (MICs) of clinical NDM-producing isolates were determined for ATM alone and CAZ/AVI+ATM using broth dilution. Restoration of the ATM breakpoint after the addition of CAZ/AVI was explored. A CAZ/AVI Etest/ATM disc method was compared with broth dilution. Results: Of 43 isolates, 33 (77%) were ATM resistant (median [range] MIC = 56 [16–512] mg/L). Addition of CAZ/AVI restored the ATM breakpoint (MIC <4 mg/L) in 29 of 33 resistant isolates (89%). Overall, the Etest/disc method correlated with the findings from broth dilution in 35 of 43 cases (81%). Etest/disc sensitivity was 77% and specificity 85%. Positive predictive value was 92% and negative predictive value 61%. Conclusion: CAZ/AVI+ATM demonstrated significant synergy in most ATM-resistant NDM-producing Enterobacterales. The Etest/disc method is a quick, reproducible, and reliable method of testing for clinically relevant synergy in the microbiology laboratory.